Pengaruh Cara Ekstraksi dari Daun Janggelan (Mesona palustris BL.) dengan Perebusan dan Pengempaan terhadap Sifat Gel - Bangun P. Nusantoro; Haryadi Haryadi (agriTECH, 2003)
A study on the effect of extraction methods on fanggelan leaf by boiling and pressing has been conducted. langgelan leaf was extracted for gel forming component by: boiling, pressing and combination of boiling and pressing. A 100 ml filtrate obtained front each extraction method was Mixed with 3 g suspension of tapioca and boiled with constant agitation. The mixture was then allowed to cool to room temperature and form a cincau gel. The gel was characterized for breaking strength and syneresis in addition to the yield that was determined for each extraction method. The extraction method with the highest yield was continued to optimize using respond surface methodology (RSM) for the best condition. The results indicated that the yield of extraction methods were 6,06% for pressing; 15,29% for boiling; 18,96% for boiling and pressing; and 22,13 % for pressing and boiling. The best condition for pressing and boiling extraction method was 275,4 kg/crn2 (pressure) for 3,2 minutes (time) which resulted gel 33,98 N (breaking strength).